How competitive is the secondary education of the OIC countries? - Mohd Arshad, Mohd Nahar (2014)
1. INTRODUCTION • The purpose of this study is to investigate the level of technical efficiency of secondary education of 16 selected OIC countries (including West Bank and Gaza). • Education efficiency has become an important issue given the pressing levels of public deficit and debt of many countries. • Since the educational sector always receives high priority in budget allocations, an evaluation of whether the allocations made for education has been technically efficient is important.